2012
DOI: 10.1200/jco.2012.42.6858
|View full text |Cite
|
Sign up to set email alerts
|

Publication of Tumor Marker Research Results: The Necessity for Complete and Transparent Reporting

Abstract: A B S T R A C TClinical management decisions for patients with cancer are increasingly being guided by prognostic and predictive markers. Use of these markers should be based on a sufficiently comprehensive body of unbiased evidence to establish that benefits to patients outweigh harms and to justify expenditure of health care dollars. Careful assessments of the clinical utility of markers by using comparative effectiveness research methods are urgently needed to more rigorously summarize and evaluate the evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
138
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(139 citation statements)
references
References 75 publications
1
138
0
Order By: Relevance
“…Approved principles of study design include blinded marker analyses and randomly selected cases (in retrospective studies) [55]. Study reporting may be negatively affected by several potential biases, and therefore adherence to standard criteria, such as Reporting Recommendations for Tumor Marker Prognostic Studies (REMARK), is essential for providing evidence on the clinical utility of biomarkers in oncology [56]. The biomarkers to be included in clinical decision making have to provide additional independent prognostic information or additive value together with established clinical and pathologic variables in a multivariate setting like the Memorial Sloan Kettering Cancer Center or Cleveland Clinic nomograms or Cancer of the Prostate Risk Assessment Postsurgical (CAPRA-S) risk stratification for PCa.…”
Section: Gene/expression Panelsmentioning
confidence: 99%
“…Approved principles of study design include blinded marker analyses and randomly selected cases (in retrospective studies) [55]. Study reporting may be negatively affected by several potential biases, and therefore adherence to standard criteria, such as Reporting Recommendations for Tumor Marker Prognostic Studies (REMARK), is essential for providing evidence on the clinical utility of biomarkers in oncology [56]. The biomarkers to be included in clinical decision making have to provide additional independent prognostic information or additive value together with established clinical and pathologic variables in a multivariate setting like the Memorial Sloan Kettering Cancer Center or Cleveland Clinic nomograms or Cancer of the Prostate Risk Assessment Postsurgical (CAPRA-S) risk stratification for PCa.…”
Section: Gene/expression Panelsmentioning
confidence: 99%
“…Greater transparency will enable others to more easily assess these claims. [6][7][8][9] Although specific methodological recommendations related to AV were excluded from the scope of this guidance document, ensuring AV before the final assessment of CV is critical to improving the evidence base for MDx tests in oncology.…”
Section: Resultsmentioning
confidence: 99%
“…More recent investigations have shown that the presence of anaplastic lymphoma receptor tyrosine kinase translocations in lung cancer and the absence of Kirsten rat sarcoma viral oncogene homolog (KRAS) mutations in colorectal cancer can predict the benefit of crizotinib and anti-epidermal growth factor receptor antibodies, respectively. Considering the critical importance of prognostic and predictive tumour markers in making clinical decisions, they should be subject to the same evidence-based standards of medicine, including cost/utility analyses, as other medical interventions and practices (1).…”
Section: Introductionmentioning
confidence: 99%